Ghosts of the Remnant: A Postcolonial Reading of the Relationship between History and Identity in Jeremiah 39–44 - Swithinbank, Hannah J. (Biblical interpretation, 2025)
The book of Jeremiah is well-known for the aporias and fractures within its text, which are much discussed. In Jeremiah 39–44 these confusions appear as indicative of two antagonistic community identities, one of which seeks (and fails) to repress the other in their claims to be the people of Israel’s God. These identities arose after the conquest of Judah by Babylon, as a shattered and divided community sought to understand their new situations. Using the postcolonial ideas of Ngũgĩ wa Thiong’o and Homi Bhabha and the historiographical work of Michel-Rolph Trouillot, I argue that in the historical narrative of this section of Jeremiah, the ghost of the Judahite community established by Gedaliah appears as a communitas interruptus, making claims on the prophet, the land, and on God, haunting and disrupting the claim of migrating golahites to be the true, surviving people of Israel’s God even as they are written out of the narrative.